Transformasi Digital dalam Strategi Pemasaran pada Industri Retail - Ibrahim, Darmawansah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the role of digital transformation in the development of marketing strategies in the retail industry. With the rapid advancement of digital technology, retail companies face new challenges and opportunities in reaching consumers effectively. Digital transformation encompasses the use of online platforms, social media, mobile applications, and analytics technologies to enhance customer experience and operational efficiency. This research employs a qualitative descriptive approach using a case study method on several retail companies in Indonesia that have implemented digital marketing strategies. Data were collected through in-depth interviews with marketing managers and observations of company documentation. The results indicate that digital transformation enables retail companies to increase customer engagement, expand market reach, and tailor product offerings based on consumer preferences analyzed digitally. Companies that successfully integrate digital technologies into their marketing strategies experience significant improvements in customer satisfaction and competitiveness. These findings emphasize the importance of digital transformation as a strategic element in modern marketing, particularly in the highly competitive and dynamic retail industry.